Prospecção de locos microssatélite e análise da variabilidade genética em uma população do Mato Grosso do Sul, visando a conservação da Arara Vermelha, Ara chloroptera (Psittacidae, Aves) - Martins, Julia Mara (Universidade Federal de São Carlos, 2007)
Several Psittacidae species, as those of Ara genus, have biological characteristics frequently associate with extinction risk. These include corporal size, specialized food preferences, low rate of population growth, restricted habitat and geographic dispersal. Genetic studies are important tools because they provide helpfulness for the conservation of those species with high extinction risks. Microsatellite markers are frequently used in population and conservation studies, and are usually isolated from the genome of the targeted species or of the related species. The main goal of this study was evaluate the genetic variation of Ara chloroptera inhabiting a touristic area, named Buraco das Araras, in Mato Grosso do Sul. For such way, six microsatellite loci were isolated and characterized and were useful to assess the genetic variation of Ara chloroptera and presented also a good value to study other Neotropical parrot. The studied population showed a genetic variation value comparable to that previously observed in a non endangered congeneric species. A significant Hardy-Weinberg disequilibrium was detected, probably related to migrants. It was hypothesized the occurrence a throughout of the years alternation of visiting individuals. The Buraco das Araras constitutes a favorable and helpful environment for reproduction and food of the red-and-green macaw and species conservation.
Keywords: Genética de populações; Ara chloroptera; Microssatélite; Variabilidade genética; CIENCIAS BIOLOGICAS::GENETICA::GENETICA ANIMAL